Perennialism and Universal Reality - Irwandra, Irwandra (Contemporary Society and Politics Journal, 2022)
The universal reality actually presents two intertwined realities, mutually reinforcing and explaining, namely the esoteric and exoteric aspects. Esotericism is the essence or substance, while exotericism is the form or format of reality itself. The perspective of perennialism does not only focus on existing diversity, but also reacts to the perspectives and attitudes of human life that have begun to be enslaved and "re-created" by advances in science and modern technology. Humans become helpless when faced with the current conditions, even though these conditions he himself has engineered. Humans in their lives are always preoccupied and trapped by the laws of relativity and measuring everything by quantities, regardless of how these conditions have led to the edge of their existence. Perennialism actually seeks to build a system of thinking that sees everything in this history as different expressions of a single Divine tradition. Faith in God, believing in the day of resurrection, and being faithful to always do good deeds is the core of all religious and theosophical teachings. A perennial and universal virtue, even though its understanding, approach and manifestation are always local and particular.